Q. 125.0( 1 Vote )

# Resolve each of t

Here, coefficient of x2 = 6, coefficient of x = -5y and constant term = - 6y2

We shall now split up the coefficient of middle term i.e., -5y into two parts whose sum is -5y and product is 6 (-6y2) = - 36y2

Clearly,

4y – 9y = -5y and,

(4y) (-9y) = - 36y2

So, we replace middle term -5xy = 4xy – 9xy

Thus, we have

6x2 -5xy- 6y2 = 6x2 + 4xy - 9xy - 6y2

= (2x – 3y) (3x + 2y)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Fill in the blankNCERT - Mathematics Exemplar

Resolve each of tRD Sharma - Mathematics

Resolve each of tRD Sharma - Mathematics

Resolve each of tRD Sharma - Mathematics

Resolve each of tRD Sharma - Mathematics